MEMPROGRAMKAN PENGENALAN BANK SYARIAH PADA DESA CIASMARA, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Mursyidah, Azizah; Anwar, Miftakhul; Wahyuni, Asri (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
This Community Service activity discusses the program to introduce Islamic Banks to the people Ciasmara Village, District Pamijahan, Bogor Regency. The aim of this community service is to provide an introduction to Islamic Banks to the people of Ciasmara Village, Distric Pamijahan, Bogor Regency. The community service method used is socialization. The result of this activity is provide knowledge to the people of Ciasmara Village, Pamijahan District, Bogor Regency about Islamic Banks in detail.